Development of the method for formation of the systemally based level of resources of logistics operations - Lutsenko, Igor; Fomovskaya, Elena (Technology audit and production reserves, 2017)
Despite its deep historical roots, at the present time there are no methods for solving logistics problems that allow to work out a unified approach to choosing the best option, relying on all relevant factors. The method of choosing the optimal parameters of the logistics stock of a logistics operation is based on the possibility of estimating the efficiency of a global economic operation model with distributed parameters. The method is based on the logistic operation model, which includes the possibility of variation by factors such as changes in the volume and price of purchases, changes in the delivery time, the possibility of accounting for changes in demand from the established mark-up and how to build the forecast. Since the demand for commodity products in open systems is of a probabilistic nature, the method involves solving a logistics problem with three probable outcomes. These outcomes are expressed in the possibility of creating models of operations of three classes: surplus operations, coordinated and deficit operations. On the basis of the proposed method, a software product is created that converts the initial data of the logistics task into a system of indicators on the basis of which it is possible to carry out an objective choice of the insurance stock size. Based on such indicators as potential effect and resource intensity, the efficiency indicator of both a separate logistic operation and the efficiency of the logistics process can be determined. The best option is determined by the results of structural and parametric optimization. Based on the results of optimization, the optimal parameters of operational forecasting are determined, the justified level of the insurance stock is selected.